2015
DOI: 10.1371/journal.pone.0122725
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis as an Early Manifestation of Subsequent Malignancy: An Asian Population Study

Abstract: Background & AimsCancer risk after appendectomy in patients with appendicitis remains unclear. This study examined the role of appendicitis as an early manifestation harbingering the distant malignancy.MethodsFrom the insurance claims data of Taiwan, we identified a cohort of 130,374 patients newly received appendectomy from 2000–2009, without cancer diagnosis. A comparison cohort of 260,746 persons without appendectomy and cancer was selected from the same database, frequency matched by age, sex, comorbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This result might imply that appendicitis, the reason for appendectomy, could be an early sign of CRC, which has also been shown in other studies. The studies conducted by Wu and Colleagues [25,26] reported that the risk tended to be elevated in shorter follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…This result might imply that appendicitis, the reason for appendectomy, could be an early sign of CRC, which has also been shown in other studies. The studies conducted by Wu and Colleagues [25,26] reported that the risk tended to be elevated in shorter follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Six retrospective studies focused on cancer (20,21,24,25,46,51). The studies had a median bias assessment score of seven (range, 5-8) stars, a median follow-up time of 12.6 (range, 1-18.6) years, and a median population of (24,25). A study with follow-up ranging from 0 to 12 months found an HR on all types of cancers of 4.6 (99.9% CI: 3.81-5.55) in favor of the control group (24).…”
Section: Cancermentioning
confidence: 99%
“…The studies had a median bias assessment score of seven (range, 5-8) stars, a median follow-up time of 12.6 (range, 1-18.6) years, and a median population of (24,25). A study with follow-up ranging from 0 to 12 months found an HR on all types of cancers of 4.6 (99.9% CI: 3.81-5.55) in favor of the control group (24). Another study with a follow-up period of 15 years (thus excluding the first 18 months) found an HR of colorectal cancers of 1.14 (95% CI: 1.02-1.28) in favor of the control group (25).…”
Section: Cancermentioning
confidence: 99%
“…55 ). Similarly, appendicitis and appendectomy have been linked to increased risk of CRC and female genital organ cancer in a relatively short period after surgery, indicating appendicitis to be an early marker of distant tumour proliferation 56,57 . Although these data come from an Asian population, it would be reasonable to offer primary screening colonoscopy to a patient who has undergone appendectomy.…”
Section: Any To-date Patient Benefits?mentioning
confidence: 99%